Pengaruh Sosio-Kultur terhadap Reformasi Hukum Keluarga Islam di Maroko - Heri Mahfudhi Mahfudhi (Institut Keislaman Abdullah Faqih Gresik, 2022)
Among the characteristics of Islamic law is that it is flexible and accommodating to the times and changing social conditions of society. This is a major factor in the efforts of several Islamic countries to make improvements to family law, which, before being contained in the puritanical classics, became codified in the format of family law. Among what was done was the country of Morocco by drafting a family law known as the Mudawwana al-Usrah. Geographically, Morocco is an Islamic country adjacent to the European region. So that culturally too much influenced by European countries. So the purpose of this study is to find information related to the influence of social culture on Islamic family law that occurs in Morocco. This study uses library research that is focused on the object of study in existing books and literature. While the method used in this research is descriptive-analytical method by providing an overview and analysis of the process of Islamic family law reform in Morocco. The results of this study indicate that the socio-cultural community of a particular region has a significant impact on legal reform. It also strengthens the paradigm that Islamic law is flexible and accommodating to the times and conditions